Retrofitting of welded structures by TIG and Plasma Dressing - Ramalho, A.L. (2022)
Due to economic and environmental constrains, the currently trend is to use the welded structures beyond their design lives. The predominant cause of in service failure of these aged structures is the fatigue of the welded joints. The use of improvement techniques in welded joints, as a repair technique, has been suggested by several authors. TIG dressing is one of the most promising of these repair techniques. However, the effectiveness of TIG remelting is closely linked to the depth of the repaired crack. The use of strain gauges can be effective to detect the presence of fatigue cracks in their initial phase of propagation, however their effectiveness in inspection programs on jobsite needs to be proven. Some TIG variants associated to recent technological innovations of fusion arc welding, are appointed to improve the penetration and the sustainability of the remelting process. In this article are presented some results of the work developed by the authors in the last years, relevant to assess the efficiency of sustainable repair, by TIG and plasma dressing, of welded structures. Relevance is given to the repair, complete or defective, of deep cracks, as well as the possible advantage of using TIG variants.